Uptake, Translocation, and Consequences of Nanomaterials on Plant Growth and Stress Adaptation - Ali, Shahid; Mehmood, Asif; Khan, Naeem (Journal of nanomaterials, 2021)
Nanotechnology has shown promising potential tools and strategies at the nanometer scale to improve food production and meet the future demands of agricultural and food security. However, considering nanotechnology’s potential benefits to date, their applicability has not yet reached up to field conditions. Increasing concerns regarding absorption, translocation, bioavailability, toxicity of nanoparticles, and impropriety of the regulatory framework restrict the complete acceptance and inclination of the agricultural sector to implement nanotechnologies. The biological function of nanoparticles depends on their physicochemical properties, the method of application, and concentration. The effects of the various types of nanoparticles (NPs) on plants were determined to increase seed germination and biomass or grain yield. The NPs also increased the plant’s resistance to various biotic and abiotic stresses. The plant’s biological functions depend on the events that occur at the molecular level. However, little progress has been made at the molecular level influenced by nanoparticles, which is an important step in evaluating potential mechanisms and plants’ effects. Therefore, it is important to understand plants’ underlying mechanism and response towards nanoparticles, and the gene expression changes through molecular approaches. The associations of nanomaterials with plant cells, the process of internalization, and the distribution of biomolecules using nanoparticles as a carrier are studied but not well understood. The transmission of biomolecules, such as nucleic acids, is a major obstacle due to cell walls, limiting the application of nanomaterials in crop enhancement mediated by genetic engineering. Recently, the use of different nanomaterials for nucleic acid delivery in plant cells has been published. Here, we aim to update researchers on the absorption and translocation of nanoparticles and elaborate on the importance of nanoparticles in agriculture and crop stress tolerance.